Pengaruh Promosi Kesehatan Terhadap Perubahan Pengetahuan Hidup Bersih dan Sehat (PHBS) Pada Tatanan Rumah Tangga Desa Lawe Loning Aman Kecamatan Lawe Sigala-Gala Kabupaten Aceh Tenggara - Nur Triningtias P (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Clean and Healthy Living Behavior (PHBS) is a form of healthy living orientation in individual, family, and community culture, which aims to improve, maintain, and protect their health both physically, mentally, spiritually, and socially. PHBS Clean and Healthy Living Behavior aims to provide learning experiences or create conditions for individuals, groups, and families, by opening channels of communication, information, and education to improve knowledge, attitudes, and behavior so that people are aware, willing, and able to transmit clean and healthy living behavior. Healthy. Through PHBS, it is hoped that people can recognize and overcome their problems and can implement a healthy lifestyle by maintaining, maintaining, and improving their health. A preliminary survey of PBHS indicators in Lawe Loning Aman Village, Lawe Sigala-Gala District, Southeast Aceh Regency, revealed that there are still many people in Lawe Loning Aman Village, Lawe Sigala-Gala District, Southeast Aceh Regency who have not implemented PHBS. This research aims to analyze the impact of health promotion on changes in clean and healthy living behavior (PHBS) in the household environment in Lawe Loning Aman Village, Lawe Sigala-Gala District, Southeast Aceh Regency, in 2023. Meanwhile, for data collection, the type of research used is quantitative with this Quasi-experiment research design using one group pretest-posttest. The instrument used was an observation sheet which was distributed to 30 respondents. The results of data analysis show that health promotion has an impact on several changes, namely the behavior of weighing babies every month (p = 0.000), hand washing behavior (p = 0.000), the behavior of using clean water (p = 0.000), the behavior of using healthy toilets (p = 0.000), mosquito larva eradication behavior (p=0.000), fruit and vegetable consumption behavior (p=0.000), physical activity behavior (p=0.000), non-smoking behavior (p=0.005). Apart from that, two variables cannot be directly influenced by health promotion, namely delivery behavior with the help of health workers (p=0.489) and exclusive breastfeeding behavior (p=0.320). Based on the findings of this research, it is recommended that health workers and other health promotion organizers improve PHBS behavior in the home environment and again interventions can be carried out aimed at further improving hygiene to avoid various diseases.